2020
DOI: 10.1097/dbp.0000000000000870
|View full text |Cite|
|
Sign up to set email alerts
|

Socioeconomic Factors Account for Variability in Language Skills in Preschoolers with Autism Spectrum Disorders

Abstract: Objective: Although no longer required for a diagnosis, language delays are extremely common in children diagnosed with autism spectrum disorders (ASD). Factors associated with socioeconomic status (SES) have broad-reaching impact on language development in early childhood. Despite recent advances in characterizing autism in early childhood, the relationship between SES and language development in ASD has not received much attention. The objective of this study was to examine whether toddlers and preschoolers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Across all outcome groups, expressive language scores were higher for infants whose mothers attained a college degree compared to infants whose mothers completed some college or less, while Receptive Language scores increased with each successive level of maternal education measured. Previous work has reported that maternal education level may be differentially related to expressive and receptive language skills (Pungello et al, 2009; although see Olson et al, 2021; Reilly et al, 2010), suggesting that the mechanisms underlying language development may differ across these domains of language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all outcome groups, expressive language scores were higher for infants whose mothers attained a college degree compared to infants whose mothers completed some college or less, while Receptive Language scores increased with each successive level of maternal education measured. Previous work has reported that maternal education level may be differentially related to expressive and receptive language skills (Pungello et al, 2009; although see Olson et al, 2021; Reilly et al, 2010), suggesting that the mechanisms underlying language development may differ across these domains of language.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has documented that supporting mothers in education beyond high school indirectly benefits their children's language development (Magnuson et al, 2009). Positive associations between maternal education level and language skills have also been found for 24-month-old ER infants with and without ASD Swanson et al, 2019) and older children with ASD (Olson et al, 2021). Most studies, however, have not explored how maternal education level interacts with behavioral predictors of language (although see Weismer & Kover, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, fMRI results could benefit from using a template that fits as many subjects as possible. Second, we did not analyze some contextual factors known to affect neurodevelopment including development in young children with ASD, such as family socioeconomic status (Olson et al, 2021a(Olson et al, , 2021b and language exposure at home. Future studies could consider these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates included in the multivariable models were informed by previous theoretical or empirical models (Olson et al, 2021 ; Thomas et al, 2012 ; Larsson et al, 2005 ) and included: age at assessment (years), English as the main language (yes (referent), no), caregiver’s highest educational qualification, marital status (married (referent), not married), race (white (referent), not white), and income.…”
Section: Methodsmentioning
confidence: 99%